BTS K-Pop consumption and self-identity in the k-pop army community of Banda Aceh - Fajriah, Nurul; Syam, Hamdani M; Susilawati, Novi; Rosemary, Rizanna; Azman, Zakirah (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The term Korean wave refers to the global spread of K-Pop, which has been widely accepted and adopted by societies around the world. The dissemination of BTS K-Pop through social media platforms such as Twitter, Instagram, music portals, and other constantly updated media channels provides extensive information for BTS fans, known as the Army. Data for this study was collected via questionnaires distributed to 133 respondents, all members of the K-Pop Army community in Banda Aceh City. The findings indicate that the consumption of BTS K-Pop influences self-concept, driven by the significant interest in BTS among fans. The appeal to Army community members is evident in the time spent watching BTS, the frequency of their engagement, and their willingness to forego other activities to watch BTS. Data analysis reveals that BTS K-Pop consumption positively affects both the physical and psychological aspects of self-concept among Army community members in Banda Aceh City, with a significance level of 5% at 1.9799.